Existence theorems for differential inclusions with nonconvex right hand side - Nikolaos S. Papageorgiou (International Journal of Mathematics and Mathematical Sciences)
In this paper we prove some new existence theorems for differential inclusions with a nonconvex right hand side, which is lower semicontinuous or continuous in the state variable, measurable in the time variable and takes values in a finite or infinite dimensional separable Banach space.